Knowledge and attitude on cardiovascular diseases among women in selected areas of Dhaka city (Asian Journal of Medical and Biological Research, 2018)
Cardiovascular diseases (CVD) are the leading cause of morbidity and mortality not only in Bangladesh but also all over the world. In Bangladesh, Women are more vulnerable group in all socio economic indexes. A cross-sectional study was conducted among 300 women from Dhaka City. Samples were chosen purposively Data were collected by semi structured self administered questionnaire. Questionnaire was based on Likert scale. Data analysis was performed by using Statistical Package for Social Science - 17.0 for windows. 75.4% respondent were in the age group of 18-35 years (Mean 30.56, Min:18 years and Max: 68 years). Majority (89%) were married & Muslim (99%) by religion, half of the participant (49.3%) were completed only primary education which indicate the poor status of women education in Bangladesh. The family size of most of the respondent (58%) are 4-6. Very few respondent have large family. It was found that 56.7 % of respondents had good knowledge, 8.3 percent had satisfactory knowledge, 1.7% had excellent knowledge and the remaining 29 percent had poor knowledge regarding cardiovascular diseases. The study revealed that among the total respondent, 99.7% women showed negative attitude & told that they would never involved in smoking. On the other hand 27.7% women show negative attitude & told that the take non smoke tobacco. Among women 56.67% respondent attitude were Moderately Favorable followed by 29% respondents were Favorable followed. Remaining 14.33% respondent attitude were favorable attitude. This study revealed that good knowledge as well as positive attitude towards major risk factors of cardiovascular diseases among the women is unsatisfactory. Socio-demographic factors for good knowledge and good knowledge for the development of positive attitude play vital role. The problem of cardiovascular diseases cannot be solved by Government alone. For effective prevention and control of cardiovascular disease, Govt. & private organization need to make integrated initiative in order to minimize the problem.Asian J. Med. Biol. Res. December 2017, 3(4): 426-431